Assessing Territorial Impact Assessment: The Case of Services of General Interest - Alina-Elena Balalia; Daniel Rauhut (European Regional Science Association (ERSA), 2012)
There is no single or common definition or even understanding of Territorial Impact Assessment (TIA). Generally, the concept is described as a method based on a multi-criteria scenario and indicator approached analysis which will provide information about the territorial impact of a policy. The conceptual background of TIA is focused on Territorial Cohesion (TC), which, in turn, also lacks a single definition. TC has a strong connection to Services of General Interest (SGI) as these services are a crucial element of the Cohesion Policy. Key elements of TC are social, economic and territorial cohesion stressing a spatial coverage as well as fair and universal access of SGI regardless which region you live in. As the definition of SGI is wide and vague, a clear classification of these services is difficult to be set. In this sense, a structured theoretical framework regarding SGI was developed within the ESPON project SeGI - Indicators and perspectives for services of general interest in territorial cohesion and development. This paper is a spin-off of the ESPON SeGI project and aims at discussing the applicability of territorial impact assessment on services of general interest. The following four research questions are proposed to be answered: (1) how does TIA relate with SGI? (2) To what extend can TIA be applied for assessing SGI? (3) Should the territorial impact be differently assessed for different SGI? (4) Are there any external factors that make TIA difficult to use for assessing the territorial impact of SGI? Previous research and EU policy documents constitute the empirical material in this study. The analysis is focused on an ex ante evaluation of TIA and on the methodology of critical evaluation. The findings suggest a rather limited applicability as an undefined concept (TIA) is based on another undefined concept (TC) to measure the impact on a vaguely defined concept (SGI). Moreover, the particularities of each SGI may be related to economic and social changes that could be or not territorially reflected. So, using TIA for all services of general interest is difficult as various external factors interfere without having a territorial impact.
Keywords: R58; O21; B40; L97; 330; regional development; Services of General Interest; Territorial Impact Assessment